Life after spinal cord injury in South African rugby: Carer and the injured individual perspective - Sandler, Joshua (My University, 2015)
Spinal cord injuries (SCI) are infrequent in rugby, however, the implications of such injuries are catastrophic and far reaching. These injuries not only affect the individual who sustains the injury but also their families, their caregivers, their community and the economy. The affected individual and their caregivers’ quality of life can be negatively affected by SCI. The effect of SCI on individuals and their caregivers has not been established in South Africa before. The main aim of this study was therefore to establish the quality of life (QOL) of rugby players and their caregivers post SCI. The specific objectives were to describe the demographic details for individuals who suffered a SCI while playing rugby, to determine the individuals’ QOL and their level of community re-integration post SCI. The study also sought to establish if a relationship exists between community re-integration and QOL following SCI. Lastly the study sought to determine the quality of life and the strain on the caregiver caring for an individual post SCI that was sustained during rugby. Method A nationwide survey was performed using questionnaires that were sent to individuals who sustained SCI while playing rugby and their caregivers.